The Effect of Storage Time on the Quality of Immersion Oil Made from Kesambi (Scheichera Oleosa) in the Image of Onion Cell Plant - Zakarias Adrianto Mautuka; Martasiana Karbeka; Monika Molina; Suratno Suratno (Department of Chemistry Faculty of Science and Technology Walisongo, 2022)
The need for immersion oil becomes very important in carrying out various laboratory analyses with a microscope to clarify the image of objects with sharp imaging. To answer this need, research has been carried out to find an alternative to immersion oil by utilizing one of the typical Alor plants that grow a lot in dry areas, namely Kesambi. In this study, the results of the immersion oil test from Kesambi which was made in 2016 were compared with the results of the retest of the same oil in 2021 and compared with standard immersion oil to determine the quality of the immersion oil. In the existing stock of Kesambi immersion oil, physical properties analysis, GC-MS, and imaging of onion cells were carried out. The results showed that the comparison of the physical properties of Kesambi immersion oil which was analyzed in 2016 and the results of the re-analysis in 2021 showed that there was no significant difference based on the parameters of density, viscosity, refractive index, acid number, and aperture value. Results GC-MS in standard immersion oil only contained 49.68% benzyl benzoic acid and reanalyzed Kesambi immersion oil found palmitic acid 12.26%, oleic acid 46.46%, stearic acid 5.26% arachidic acid 13, 84%, and other spectra were detected as impurities. Although there were impurities and differences in fatty acid content between the standard immersion oil and the immersion oil from Kesambi that had been stored for five years, there was no difference in the imaging results of onion cells.